2017
DOI: 10.1007/s00300-017-2133-0
|View full text |Cite
|
Sign up to set email alerts
|

Low abundance and high species richness: the structure of the soft-bottom isopod fauna of a West Antarctic glacial fjord

Abstract: Isopods belong to the most speciose groups of the Antarctic benthic fauna, although the knowledge on their diversity and small-scale distribution patterns is still limited. Here we analyze the diversity of the isopod fauna in the Admiralty Bay, a glacial fjord on the King George Island. The basin is located in the region of the Antarctic Peninsula, the fastest warming area of the Southern Ocean. The study provides important baseline data for future research, particularly with respect to temporal fluctuations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Only Cryosignum incisum (Richardson 1908) was found in the shallowest sublittoral and it seems that this species is generally associated only with the shallower sublittoral zone (Doti et al 2005). Most of the species found in our study were singletons, doubletons and tripletons, which supports earlier results from the Admiralty Bay soft bottom (Zemko et al 2017) and other studies showing low densities of the Antarctic isopods (Richardson and Hedgpeth 1977;Brandt 2001), although it is worth mentioning that van Veen grab is not a perfect tool for isopod sampling. A higher number of individuals was found only for Eurycope crassiramis Golovan, 2008 and Coulmannia australis Hodgson, 1910, however both species were found in two samples only.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Only Cryosignum incisum (Richardson 1908) was found in the shallowest sublittoral and it seems that this species is generally associated only with the shallower sublittoral zone (Doti et al 2005). Most of the species found in our study were singletons, doubletons and tripletons, which supports earlier results from the Admiralty Bay soft bottom (Zemko et al 2017) and other studies showing low densities of the Antarctic isopods (Richardson and Hedgpeth 1977;Brandt 2001), although it is worth mentioning that van Veen grab is not a perfect tool for isopod sampling. A higher number of individuals was found only for Eurycope crassiramis Golovan, 2008 and Coulmannia australis Hodgson, 1910, however both species were found in two samples only.…”
Section: Resultssupporting
confidence: 91%
“…It was already suggested that the high diversity of habitats (including different types of soft and hard bottom, macroalgae forests) and dynamic set of environmental properties can be a reason of high diversity of the Admiralty Bay macrofauna in many taxonomic groups . High diversity of habitats can be vitally important in the case of isopods, because their distribution in the Admiralty Bay is very patchy and most of the species were rare (Zemko et al 2017). Therefore, there is a need for further studies based on large sampling effort, and exploration of different types of habitats.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations